1984
DOI: 10.1111/j.1943-278x.1984.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Economic Business Cycles on United States Suicide Rates

Abstract: A number of social science investigators have shown that a downturn in the economy leads to an increase in the suicide rate. However, the previous works on the subject are flawed by the fact that they employ years as their temporal unit of analysis. This time period is so large that it makes it difficult for investigators to precisely determine the length of the lag effect, while at the same time removing the autocorrelation effects. Also, although most works on suicide and the business cycle employ unemployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…The parallelism between suicide rates and unemployment rate was evident for the period 1953-72 in both men and women (Fig. 2), which is in keeping with other findings (Vigderhous & Fishman, 1978;Boor, 1980;Kreitman & Platt, 1984;Platt, 1984;Platt & Kreitman, 1984;Wasserman, 1984;Cormier & Klerman, 1985). However, the correlation between suicide rates and unemployment rate weakened in men and became negative in women for the period 1973-86.…”
Section: Discussionsupporting
confidence: 90%
“…The parallelism between suicide rates and unemployment rate was evident for the period 1953-72 in both men and women (Fig. 2), which is in keeping with other findings (Vigderhous & Fishman, 1978;Boor, 1980;Kreitman & Platt, 1984;Platt, 1984;Platt & Kreitman, 1984;Wasserman, 1984;Cormier & Klerman, 1985). However, the correlation between suicide rates and unemployment rate weakened in men and became negative in women for the period 1973-86.…”
Section: Discussionsupporting
confidence: 90%
“…Several authors have pointed out the correlation between suicide rate and economy fluctuations. [56][57][58][59][60] Several studies have suggested a trend of regional suicide rate differences, consistent with those of unemployment rates or other socioeconomic index in Japan. [61][62][63] Archer and Gartner have reported that the correlation between homicide rates and unemployment rates varies from nation to nation.…”
Section: Discussionmentioning
confidence: 95%
“…Breault and Barkey (1982) reported that deaths due to political violence (their measure of political integration) in 42 nations during the 1960s were inversely related to crude suicide rates. While Boor (1982) found support for Durkheim's theory of political integration, Marshall (1981) and Wasserman (1984a; 1984b) report that political integration is indirectly related to suicide because political crises stimulate economic activity, which in turn lowers the suicide rate. We examine, therefore, unemployment and annual percentage change in the gross domestic product per capita in our analysis.…”
Section: Theoretical and Literature Reviewmentioning
confidence: 97%